Rancang Bangun Prototipe Sistem Otomatisasi Pengereman Elektromagnetik Berbasis Mikrokontroler Dengan Kontrol PID - Mohammad Hafiz Hersyah; Firdaus Firdaus; Hamidatul Nesya (Universitas Andalas, 2018)
Braking Automation system is needed to make people do their job in braking while driving. This paper aims to design and construct an electromagnetic braking automatic system that able to make car stopped before colliding a barrier by applying of the Proportional Integral Derivative (PID) method. To find out how the effective utilization of PID control on electromagnetic braking automatic will be compared with the results of braking without using PID. Determination tuning result of controller PID parameter obtained by using the trial and error methods and obtained the PID parameter values that suitable are Kp = 2.98, Ki = 0.104 and Kd = 1.35. The ultrasonic sensor used as detection the distance to a barrier. From the testing results of electromagnetic braking system with PID control more effective than with the electromagnetic braking system without PID because it can be seen from the side cessation of the car approaching set point, the results of the electromagnetic braking with PID control better than the electromagnetic braking without PID control.